1957
DOI: 10.3181/00379727-95-23286
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effect of D-Ribose in Man

Abstract: Ribose 5-phosphate occupies an important position as an intermediate in the oxidative or pentose phosphate pathway of glucose metabolism. In both plant and animal tissues ribose 5-phosphate forms fructose 6-phosphate ( 1 ) which may be readily converted to glucose. Recently Agranoff and Brady(2) have isolated an enzyme from mammalian liver capable of phosphorylating D-ribose to form ribose 5-phosphate, thus permitting ribose to enter into this pathway. The conversion of ribose to glucose has been demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1958
1958
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…After infusion of D-xylOse and L-arabinose in man a rise in blood glucose has been observed (10). Little or no change occurs upon infusion of D-arabinose or D-lyxose, whereas D-ribose has been observed to cause marked decreases in blood glucose level (17). Despite the hypoglycemia induced by ribose, D-ribose-i-C"4 has been shown to be converted to blood (16) and urinary glucose (12) via the pentose phosphate pathway.…”
Section: Discussionmentioning
confidence: 90%
“…After infusion of D-xylOse and L-arabinose in man a rise in blood glucose has been observed (10). Little or no change occurs upon infusion of D-arabinose or D-lyxose, whereas D-ribose has been observed to cause marked decreases in blood glucose level (17). Despite the hypoglycemia induced by ribose, D-ribose-i-C"4 has been shown to be converted to blood (16) and urinary glucose (12) via the pentose phosphate pathway.…”
Section: Discussionmentioning
confidence: 90%
“…The effect of ribose on blood levels of glucose, pyruvate and inorganic phosphate It has been reported that the infusion of ribose into the normal and some diabetic individuals causes a lowering of blood glucose of about 30 mg. per cent (14). A typical response of blood glucose to ribose is demonstrated in Figure 7 of ribose is shown again in the same subject ( Figure 5) after a 4 Gm.…”
Section: The Urinary Excretion Of Ribosementioning
confidence: 89%
“…This paper presents data concerning the fate of ribose after its intravenous administration in both unlabeled and C14 labeled form to both normal and diabetic subjects. Preliminary results of these studies have been published (13), as well as a report of the hypoglycemia induced by ribose infusion (14). Previous publications (15,16) from this laboratory have described the physiologic disposition in man of the related pentoses D-Xylose, D-and L-arabinose, and D-lyxose, as well as the effects of insulin on the blood levels of these sugars.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Segal and Foley [21,22] found different levels of hypoglycemia with D-ribose supplementation depending upon dose with higher doses producing a greater decrease. Gross et al [23] has published similar findings.…”
Section: Discussionmentioning
confidence: 99%